State and Society in Small-town Russia : A Feminist-ethnographic Inquiry into the Boundaries of Society in the Finnish-Russian Borderland - Kulmala, Meri (Deaprtment of Social Research, 2013)
This study explores state-society interrelations in contemporary Russia through citizens involvement in civil society by asking: What kinds of organizational civic activities occur? How are these forms of civic activity interwoven with the state and public structures? Finally, why do particular forms occur? The state-society relationship is analyzed through the following concepts: 1) state-society patterns, 2) role of civil society organizations, 3) transnational interaction, and 4) gender. Instead of the conventional sectoral thinking, the society is treated as spaces interdependent of one another. Messy conceptions of civil society and the state are opened up empirically. The analysis is grounded on an extensive ethnographic investigation within the Sortavala district (incl. villages) in Russian Karelia. The data includes more than 150 interviews; participant observation in many events; over 500 pages of field notes; and documents. Sortavala s location on one hand in Russian Karelia, outside big Russian cities, and on the other hand on the border of Finland and the EU allows a fascinating view that is peripheral and transnational at the same time. By zooming in on a very local setting allows revealing what really goes on concerning the studied relationship in its daily practices. Nevertheless, the analysis is not restricted to this micro world but is extended to a larger macro-level environment. The study performed a thorough consideration of a wide set of citizens organizations, explored the understanding and disaggregation of the state, thus concentrated on both sides of the studied relationship, and focused on the boundaries and convergences of those two spheres. In doing so, it diversified the rather stereotypical picture of the weak and apolitical Russian civil society co-opted by the state. The research showed complexities of the Russian state-society relationship: perhaps the most compelling finding concerns the significant overlap and interdependence between the state structures and civil society ...